Active Learning in Introductory Economics: Do MyEconLab and Aplia Make Any Difference? - Trien Nguyen; Angela Trimarchi (International Journal for the Scholarship of Teaching and Learning, 2010)
This paper reports experiment results of teaching large classes of introductory economics with modern learning technology such as MyEconLab or Aplia. This new technology emerges partially in response to the enrollment pressure currently facing many institutions of higher education. Among other things, the technology provides an integrated online teaching and learning environment that allows active learning through student direct participation in the learning process as well as interaction with their instructor, peers, and the outside Internet. Our results showed that, for the classes in the experiment, modern learning technology could make a difference in helping students improve their class mark averages by a small but statistically significant amount of 2% regardless whether the technology was used as a required or optional course component. We noted that students responded more favorably when the technology component was given more weight in the marking scheme.